Maqasid syariah dalam pengagihan zakat asnaf Al-Gharimin di institusi-institusi zakat di Malaysia - Ismail, Halim; Daud, Mohd Noor (Jabatan Wakaf, Zakat dan Haji, Jabatan Perdana Menteri, 2017)
This study is aimed at describing the implementation of zakat distribution on asnaf al-Ghārimīn in zakat institutions in Malaysia based on maqāṣid syarīah. This study uses qualitative methods and analyzes using inductive, deductive and comparative methods. Studies show that zakat institutions in Malaysia have implemented zakat distribution on asnaf al-Ghārimīn based on maqāṣid syarīah. Improvement in terms of the distribution of maqāṣid syarīah based on the distribution of the distribution is very important to overcome the problem of asnaf al-Ghārimīn in the institutions of zakat in Malaysia.This study implies the implementation of zakat distribution on asnaf al-Ghārimīn by zakat institutions in Malaysia.